2009
DOI: 10.1016/j.sigpro.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Using labeled data to evaluate change detectors in a multivariate streaming environment

Abstract: We consider the problem of detecting changes in a multivariate data stream. A change detector is defined by a detection algorithm and an alarm threshold. A detection algorithm maps the stream of input vectors into a univariate detection stream. The detector signals a change when the detection stream exceeds the chosen alarm threshold. We consider two aspects of the problem: (1) setting the alarm threshold and (2) measuring/comparing the performance of detection algorithms. We assume we are given a segment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…A time point where some characteristic of a time series changes is called a change-point. The detection of change-points is a typical problem of time series analysis [59,[61][62][63][64]; in particular it provides a segmentation of time series into stationary segments. In this section we suggest an ordinal-patterns-based method for change-point detection.…”
Section: Ordinal-patterns-based Segmentation Of Eeg and Clustering Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…A time point where some characteristic of a time series changes is called a change-point. The detection of change-points is a typical problem of time series analysis [59,[61][62][63][64]; in particular it provides a segmentation of time series into stationary segments. In this section we suggest an ordinal-patterns-based method for change-point detection.…”
Section: Ordinal-patterns-based Segmentation Of Eeg and Clustering Ofmentioning
confidence: 99%
“…This is a classical problem of change-point detection (see Section 1.1.2.2 in [59]); to solve it, we compare the value of CEofOP( t * ; d) with a certain threshold h: if CEofOP( t * ; d) ≥ h then one decides that there is a change-point in t * , otherwise it is concluded that no change has occurred. We compute the threshold h using block bootstrapping from the sequence of ordinal patterns (see [63,64] for a comprehensive description of the block bootstrapping; since this approach is rather often used we do not go into details). The solution of Problem 1 using the CEofOP statistic is described in Algorithm 1 (Appendix A.1).…”
Section: Definition 9 the Ceofop ("Conditional-entropy-of-ordinal-pamentioning
confidence: 99%
“…On the contrary, the higher h, the higher the possibility of false rejection of the H A is. As it is usually done, we consider the threshold h as a function of the desired probability α of false alarm; for computing the threshold h(α) we use block bootstrapping from the sequence π d,L of ordinal patterns (bootstrapping is often used in change-point detection for computing a threshold, see [44,45] for a theoretical discussion and [46,47] for applications of bootstrapping with detailed and clear explanations). Namely we shuffle blocks of ordinal patterns from the original sequence, in order to create a new artificial sequence.…”
Section: Algorithm For Change-point Detection Via the Ceofop Statisticmentioning
confidence: 99%
“…Change point analysis is also used in the detection of credit card fraud (Bolton and Hand [2]) and other anomalies. In practical applications, the applications of change point also be found in signal processing: where change point analysis can be used to detect significant changes within a stream of images (Kim et al, [9]). …”
Section: Nonparametric Bayesian Approach and Change Pointmentioning
confidence: 99%